Study of Construction Techniques Applied to the Vivaldi Antipodal Antenna - Figueredo Sobrinho, Raimundo Eider; de Oliveira, Alexandre Maniçoba; Nurhayati, Nurhayati; Justo, João Francisco (Journal of Intelligent System and Telecommunication, 2024)
This article examines the evolution and construction techniques of the Vivaldi antipodal antenna (AVA), a broadband antenna utilized in a range of applications, including microwave medical imaging systems (MMIS), radars, and 5G communications. The article examines the operational characteristics of the AVA and the impact of substrate dielectric properties on its performance, as well as analyzes various construction techniques employed in the development of the AVA, including the use of directors, dielectric lenses, and metamaterials, antenna arrangements, and resonant and radiating cavities. It elucidates the advantages and disadvantages inherent to each approach.